Enhancing Information Transmission Methods Using Femtosecond Radiation - Hnatenko, O. S.; Chaplyhin, V.; Kravchuk, O. (My University, 2024)
In telecommunications, there is increasing interest in developing stable sources for the third fiber optic transmission window, particularly ring fiber lasers with passive mode-locking. Erbium-doped optical fibers, operating at a wavelength of 1550 nm, play a key role in this field. It is expected that these lasers will eventually replace many semiconductor data transmission lasers used in Dense Wavelength Division Multiplexing (DWDM) systems according to the ITU frequency grid.
Keywords: Femtosecond Radiation; optical fiber; Optical Methods; mode-locking